Electrospun PAN@Ferrites Nanofibers for Rectifier and Humidity Devices - Ban Abbas Rijah; Iftikhar M. Ali (Iraqi Journal of Physics)
Zinc cobalt ferrite (ZnCoFe2O4) and zinc ferrite (ZnFe2O4) were prepared using the sol-gel synthesis. composite materials, PAN@CoFe2O4 and PAN@ZnCoFe2O4, were created by combining polyacrylonitrile (PAN) polymer with ZnCoFe2O4 and ZnFe2O4. Electrospinning was used to apply thin coatings onto glass and p-Si wafers. The synthesized fibre for both pure PAN polymers and their ferrite-based composites was illustrated in Field Emission Scanning Electron Microscopy (FESEM) images. The X-ray diffraction (XRD) analysis reveals that the PAN polymer exhibits a prominent peak at a precise angle of 29. 3345°.The size of this peak remains constant in PAN composites containing ZnCoFe2O4 and CoFe2O4. Fourier transformer infrared (FTIR) shows that absorptions have stretching vibrations between metal and oxygen. Nanofiber composites display non-ohmic characteristics, as evidenced by current-voltage (I-V) tests. PAN nanofibers display conductive properties, whilst their ferrite composites demonstrate rectification behaviour at room temperature when subjected to a low applied field. For PAN NFs, there is no effect when relative humidity percentage increases and decreases, but with adding ferrite materials PAN@ZnFe2O4 and PAN@ZnCoFe2O4 where, there is a significant change in resistance when humidity increases and decreases.